2012
DOI: 10.1016/j.breast.2012.02.004
|View full text |Cite
|
Sign up to set email alerts
|

What factors may influence psychological well being at three months and one year post BRCA genetic result disclosure?

Abstract: Genetic testing for breast cancer predisposition has been available in the clinical practice for more than a decade. How the result of genetic testing affects the psychological well-being of the individuals is an under-researched area in many populations. Follow-up analysis of psychological well-being via HADS scale was performed in 364 individuals at 3 months and 1 year after the disclosure of BRCA1/2 genetic result. We analyzed potential predictors for pathological anxiety and variables associated to the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 29 publications
4
38
0
2
Order By: Relevance
“…53 Other studies have not reported any change in psychological risk with positive test results. 32,33,40,[57][58][59][60][61][62] Nonetheless, women who test positive for BRCA1/BRCA2 are also often met with resistance, shock, and other negative emotions from family members. [63][64][65][66] Similarly studies of individuals undergoing HNPCC testing demonstrate that the individual experiences of both unaffected and affected carriers are varied, but the majority experience an overall decrease in anxiety and depression.…”
Section: Impact Of Genetic Test Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…53 Other studies have not reported any change in psychological risk with positive test results. 32,33,40,[57][58][59][60][61][62] Nonetheless, women who test positive for BRCA1/BRCA2 are also often met with resistance, shock, and other negative emotions from family members. [63][64][65][66] Similarly studies of individuals undergoing HNPCC testing demonstrate that the individual experiences of both unaffected and affected carriers are varied, but the majority experience an overall decrease in anxiety and depression.…”
Section: Impact Of Genetic Test Resultsmentioning
confidence: 99%
“…The most robust predictor of future distress is distress at baseline. 32,49,[57][58][59]68,[74][75][76][77] Additional risk factors include prior psychiatric history of depression, 74 history of using psychotropic medications, 75 passive or avoidant coping styles, 51,75,[80][81][82] or inaccurate risk perception, [85][86][87] which put individuals at risk of experiencing distress throughout the process or many years after receiving their results. Other important risk factors for future distress include being the first member of the family to obtain genetic testing, 33 having children, 76 experiencing the death of a relative from hereditary cancer, 34,78 as well as experiencing unresolved loss 5 and complicated grief.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations